Exploring the Influence of Transformational Leadership on Educational Outcomes in Muhammadiyah Schools - A'yun, Ummu Qurrota; Sulisworo, Dwi (Contemporary Education and Community Engagement (CECE), 2024)
Transformational educational leadership is pivotal in the advancement of Muhammadiyah Schools, which aim to promote empowerment and social change as Islamic educational institutions. This research investigates the practices and effects of transformational educational leadership within Muhammadiyah schools. Utilizing a qualitative approach, data were gathered through comprehensive interviews with principals, teachers, and staff from various Muhammadiyah schools in select regions. The analysis shows that transformational educational leadership in these schools is marked by a strong dedication to reinforcing Islamic identity, improving educational quality, and encouraging positive social change. School leaders serve as change agents, motivating and empowering staff and students to reach broader educational objectives. They employ inclusive and participatory methods, rooted in Islamic values, for decision-making and policy development. The effects of transformational educational leadership are evident in academic enhancement, character development, and the instillation of Islamic values-based character. Furthermore, fostering an inclusive and empowering school culture leads to harmonious relationships among the schools, students, teachers, and the community. This study offers a deeper insight into the role and practices of transformational educational leadership in Muhammadiyah schools. The practical implications highlight the necessity of bolstering leadership and credibility founded on Islamic values to improve educational quality and make meaningful societal contributions.